Pengaruh Penerapan Metode As-Shidiq terhadap Kemampuan Membaca Al-Qur`an Siswa di MI Narrative Qur`an Lamongan - Muflich, Moch Faizin (Universitas Nahdlatul Ulama Pasuruan, 2022)
This research is based on several objectives, namely: 1) How is the application of the As-shidiq method at MI Narrative Quran Lamongan. 2) How is the ability to read the Qur'an of students at MI Narrative Quran Lamongan. 3) How is the effect of the application of the As-shidiq method on ability reading the Koran of students at MI Narrative Quran Lamongan. This research method uses a quantitative approach in the form of correlational research to determine the existence of a relationship between the variables studied. The results of this study can be concluded into three,namely the application of the As-shidiq method at MI Narrative Quran Lamongan which is evidenced by the results of the questionnaire showing a value of 76.8% and this score is quite good, students' ability to read the Koran at MI Narrative Quran Lamongan as evidenced by the test results show the value of 82.9% and this value is classified as good, the effect of the application of the As-shidiq method on students' ability to read the Qur'an at MI Narrative Quran Lamongan has a significant effect as evidenced by a significance value of 0.000 <0.05.